Using Robotics to Support the Acquisition of STEM and 21st-Century Competencies: Promising (and Practical) Directions - Stokes, Allyson; Aurini, Janice; Rizk, Jessica; Gorbet, Robert; McLevey, John (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
To enhance how educators use robotics to support the development of STEM and 21st century competencies, we report findings from focus groups and interviews with 133 elementary teachers and 46 elementary students, 19 video-recorded classroom observations, and a teacher survey from Ontario, Canada. We find that teachers use robotics in a variety of ways to support the development of cognitive, interpersonal, and intrapersonal skills. Despite the potential benefits, our participants identified several factors that limit the adoption of robotics teaching and learning on a wider scale, including insufficient curriculum and assessment integration, resources, and professional development and support. We provide practical policy guidelines to support the broader integration of robotics and reflect on how these recommendations may inform teaching and learning in a (post-) COVID-19 classroom.